Hardware and Eco-Feminist Art : Hacking and Artistic Practices Towards Ethical Technology - Patrícia J. Reis; Stefanie Wuschitz (transcript, 2025)
It is an open secret that the hardware in our smart devices contains plastics and raw materials mined from conflict regions. Can we move beyond this oppressive system of extraction to find ethical alternatives? Feminist hackers Patrícia Reis and Stefanie Wuschitz discuss developing technology through eco-feminist artistic tools, rooted in care economies, local knowledges and collective survival. Through an intensive knowledge-sharing process and collaboration with peers, they unpack eco-feminist theory and practices to propose resistance strategies grounded in ethical hardware and de-growth economies – contributing significantly to the new field of arts-based research.